Evaluation of Social Forestry Program Activities in HKM Ake Guraci Marikurubu District Ternate City - Tiamuaida, Tiamuaida; Niapele, Sabaria; Putri, Wiwin Failysa (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
This research aims to determine the suitability of the Social Forestry Program with the Implementation of Social Forestry Activities in HKm Ake Guraci, Marikurubu District, to determine the Inhibiting Factors of the Social Forestry Program in HKm Ake Guraci, Marikurubu District. The research was conducted at HKm Ake Guraci, Marikurubu Village. The research time is approximately 2 months in October-November 2023. This research uses qualitative descriptive methods. Data sources, primary data and secondary data. Data collection techniques include observation, interviews, documentation and literature study. Conclusion: The inhibiting factors for the Social Forestry Program at HKm Ake Guraci are: Lack of budget to finance programmed activities so that the planned program cannot run as it should and lack of availability of raw materials which results in delays in product production activities at HKm Ake Guraci. KUPS. Suggestion: Both central and regional governments can allocate budgets so that planned activities can be implemented well. To KPH Ternate Tidore to further increase cooperation with other agencies so that the planned program can be realized. To KPH Ternate Tidore to make an annual work plan so that the planned program can be structured every year. For students, as a reference for further research.